In the beginning were stories, not texts story theology - Song, Choan-Seng, 1929- (Cambridge : James Clarke, 2012)
Stories are the most basic mode of human communication. Writers, painters, sculptors, artists, and indeed, people of all walks of life live by the telling of their stories. Christianity itself is deeply rooted in storytelling - the vast majority of the Hebrew Scriptures, for example, consist of stories, and Jesus proclaimed and taught about the Reign of God through stories and parables. At the heart of the Christian faith are stories, not concepts, propositions, or ideas. In the Beginning Were Stories, Not Texts laments the fact that Christian theology is all too often expressed in terms of abs.
Story 4: "Is it I, Lord?" (Mark 14:19)Story 5: "Have nothing to do with that innocent man" (Matt 27:19); Story 6: "Daughter of Jerusalem, do not weep for me"; Story 7: "Not what I want, but what you want" (Mark 14:36); 8. Stories Are Culturally Distinctive; Stories are culturally distinctive; The Kannon Who Substituted; The Keys of Destiny; The ugly duckling; 9. Stories Can Be Theologically Interactive; Suffering and faith; Alicia's Story; Sin and death; Death in the Garden; "Have You Eaten from the Tree?"; Transformation; "Take, this is my body"; "We Have Drunk Soma, Have Become Immortal."
Includes bibliographical references.
Print version record.
Master record variable field(s) change: 072
Keywords: Theology; Storytelling -- Religious aspects -- Christianity; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; Storytelling -- Religious aspects -- Christianity; Theology; RELIGION / Christianity / General; Electronic books